Fast Low Voltage Ferroelectric Liquid Crystal for Field Sequential Color Display - Guo, Qi; Fan, Fan; Murauski, Anatoli; Yao, Lishuang; Chigrinov, V. G. (Photonics Letters of Poland, 2011)
In this paper, a fast responded ferroelectric liquid crystal (FLC) driven with low voltage is achieved. The switching time and contrast ratio of two different FLC materials are investigated with the temperature range from room temperature to 80°C. The switching time of 50?s and contrast of 300:1 are obtained with FLC595 with 5V voltage at room temperature, and switching time decreases with higher temperature. Compared to FLC595, FD4004N has a larger temperature range and different optimal temperature of about 40°C, at which the contrast is 360:1. Proposed ferroelectric liquid crystals show excellent properties which is highly promising for future applications. Full text: PDF References: M.A. Handschy, B.F. Spenner, "The Future of Pico Projectors", Inf. display Vol. 24 No. 12 (2008). DirectLink M.J. O?Callaghan, R. Ferguson, R. Vohra, W. Thurmes, A.W. Harant, C.S. Pecinovsky, Y.Q. Zhang, S. Yang, M. O?Neill, M. A. Handschy, " ",J. Soc. Info. Display 17, 369 (2009). [CrossRef] M.A. Handschy and James Dallas, "9.5L: Late-News Paper: Scalable Sequential-Color Display Without ASICs", Display Devices 6, 8 (2007). [CrossRef] E. H. Stupp, M.S. Brennesholtz, " Projection Displays (Wiley, Chichester 1999)." X.J. Yu, H.S. Kwok, , "Application of Wire-Grid Polarizers to Projection Displays", Appl. Opt. 42, 6335 (2003). [CrossRef] H.C. Huang, B. Zhang, H. Peng, H.S. Kwok, P.W. Cheng, Y.C. Chen, "Processes, characterizations, and system applications of color-filter liquid-crystal-on-silicon microdisplays", J. Soc. Info. Display 14, 499 (2006). [CrossRef] V.G. Chigrinov, Liquid Crystal Devices: Physics and Applications (MA Artech House, Boston 1999). M.J. O?Callaghan, R. Ferguson, R. Vohra et al., "Bistable FLCOS Devices for Doubled-Brightness Micro-Projectors", SID Symposium Digest 39, 232 (2008). [CrossRef] E. Pozhidaev, V.C. Chigrinov, X.H. Li, "Photoaligned Ferroelectric Liquid Crystal Passive Matrix Display with Memorized Gray Scale", Jpn. J. Appl. Phys. 45, 875 (2006). [CrossRef] [10] E. Pozhidaev,V.C. Chigrinov, T. Du, S. Kotova, M. Minchenko, V. Vashchenko, A. Krivosey, F. Fan, Proc. Eurodisplay Conference 41 (2009). X.H. Li, A. Murauski, A. Muravsky, P.Z. Xu, H. L. Cheung, V.G. Chigrinov, "Grayscale Generation and Stabilization in Ferroelectric Liquid Crystal Display", J. Display Techn. 3, 273 (2007). [CrossRef] R. Kurihara, H. Furue, T. Takahashi, T. Yamashita, J. Xu, S. Kobayashi, "Fabrication of Defect-Free Ferroelectric Liquid Crystal Displays Using Photoalignment and Their Electrooptic Performance",Jpn. J. Appl. Phys. 40, 4622 (2001). [CrossRef] S.T. Lagerwall, Ferroelectric and Antiferroelectric Liquid Crystals (Wiley-VCH, New York 1999). [CrossRef]